Hematological parameters in patients with acnes - Chen, Tingqiao; Chen, Yangmei; Shao, Xinyi; Chen, Jiayi; Liu, Lin; Li, Yuxin; Pu, Yihuan; Chen, Jin (Journal of cosmetic dermatology, 2023)
Objective To compare complete blood count (CBC) parameters and inflammatory factors in the patients with different grade of acne vulgaris and healthy controls. Methods A total of 20 patients were enrolled in this study. Patients were divided into mild group and moderate‐to‐severe group based on the acne severity, and compared to controls. Inflammatory factors (TNF‐α, IL‐6, IL‐8, and IL1‐α) detected by ELISA and complete blood count parameters (MPV, NLR, dNLR, PLR, LMR, and SII) obtained by routine blood tests were compared among the three group. Results All CBC parameters were not significantly elevated in patients with acne compared to healthy controls. However, the present studies have found that the inflammatory factors in acne patients were significantly elevated relative to healthy controls, and increase with the acne grade. Conclusions Inflammatory factors are convenient parameters to show inflammatory response to acne vulgaris, and may be a new clinical method for judging the acne grades of objectively. Considering the use of antibiotic, we believe that this metric worth further study.